Implementation of Number Block Game Techniques for Learning Number Symbol in Early Childhood - Muhammad Munif; Muhammad Sali; Zaenol Fajri; Mahmuda Mahmuda; Tutik Farlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The low ability to recognize number symbols in children aged four to five years is a problem that has always been a hot conversation between educators, parents, and the general public. Children aged 4 to 5 years should recognize the number symbols one through ten. The purpose of this study is how the number block game technique is used to recognize number symbols in children aged four to five years. This type of research is qualitative-descriptive using a case study approach. The results showed that using the number block game can create a fun learning atmosphere, make it easier for children to absorb learning material, especially in recognizing number symbols, and make children feel happy and at ease. The teacher ensures that the learning objectives are met during the learning activities. The findings of this study indicate that the use of number block game techniques to improve the ability to recognize number symbols in children aged four to five years can be carried out effectively and efficiently.